Cultural activities, innovative milieus and urban policies: a comparison of two districts in the city of Lisbon - Costa, Pedro (2012)
This paper explores the relation between cultural-led territorialized production complexes and the mechanisms behind the creative dynamics which are found there, focusing on some conclusions of two case studies conducted in Lisbon, Portugal: the ‘Bairro Alto – Chiado’ area (a typical cultural quarter in the historical center of the city), and the ‘Parque das Nações’ district (a recently regenerated old industrial area). The analysis centers on the ‘milieu’ effects, the innovation dynamics and the governance modes specifically developed in those areas so as to shed light on the mechanisms behind their sustainability and competitiveness. Drawing on these highly contrasting experiences, some general assumptions are emphasized on the relation between territory and the development of successful local production systems based on cultural activities.